Perfil de idosos que buscam vagas para cuidados diurnos - Semensato, Carolina Ramos (Universidade Federal de São Carlos, 2021)
Introduction: Aging is one of the biggest public health challenges. It is a heterogeneous, universal, natural, and constant process, inherent to the human condition, characterized by several biopsychosocial changes in people's lives. It is an ascending phenomenon in Brazil and in the world, thus generating new needs and challenges, in addition to reformulations in public policies, aimed at reconciling longevity and quality of life with dignity and respect. Due to the projections of greater longevity in the Brazilian context, it is necessary to allocate resources in places of social support and appreciation of family ties, such as the Day Centers for the Elderly (CDI). CDIs, like daycare units of medium complexity of the special social protection network, are part of the social support network and promote socialization, strengthening the health-promoting mechanism. Objective: To characterize the profile of elderly people looking for daycare vacancies in the context of Long Stay Institutions for the Elderly (ILPI) in two inland cities of São Paulo, as well as the applicant for the vacancy and the reason for such search. Methodology: This is a descriptive, qualitative study with content analysis principles, which were applied in the light of the thematic theoretical framework. The data comes from the database of the research group “Direito, Cidade e Envelhecimento” linked to the Department of Gerontology (DGero) of the Federal University of São Carlos (UFSCar). The work development was organized in 3 stages, the first being the appropriation of the theme and bibliographic deepening with the intersection of descriptors in the selected databases, identifying bibliographic productions close to the subject of the study. The second stage was related to the pre-analysis and initial reading of the data, focusing on the characterization of the general profile of the elderly (gender, age group, marital status), who sought the vacancy, and the reason for the search. The third step concerned the treatment of the obtained results and interpretation. The results indicated 451 scientific productions, of which the reading of titles and abstracts supported the exclusion of 446 due to theme incompatibility, resulting in the identification of 5 scientific articles whose studies were aligned with the theme related to the public profile connecting with the elderly people who seek support from CDI. In addition, it was found that some Long Stay Institutions for the Elderly (ILPI) offer vacancies for the CDI modality. Of the 214 requests for both modalities, 189 (88.31%) were for ILPI and 25 (11.68%) for CDI. Of those for CDI, 23 (92%) were from the city of Araraquara and 2 (8%) were from the city of São Carlos. In both cities, the prevalence was female 18 (72%) with a mean age of 84 years, followed by 7 requests (28%) for males with a mean age of 78 years. As for marital status, widowhood was prevalent in 18 (72%) of the requests. Still, in the family context, it was found that most elderly people have children 21 (84%) and 8 (32%) live alone. According to the applicant, the majority 18 (72%) need small support in daily life and support for mobility. The prevalence of applicants is female 21 (84%), with daughters 14 (56%) married 11 (44%) and an average age of 59 years for both sexes. As for the reasons for searching for the vacancy, the prevalence was related to socialization with 13 (52%), followed by health 8 (32%), safety 2 (8%), and 2 (8%) who did not inform. Discussion and Conclusion: The profile of the elderly person seeking a place for a CDI is predominantly female, aged over 80 years, widow, and partially dependent. About the applicant for the vacancy, most were the daughters for reasons of socialization, assistance in daily activities, and mobility. In addition, the search for CDI in the ILPI modality may indicate weaknesses in understanding the typology of services, or the absence of this type of service in the city, signaling demands for partial care attention that favor the maintainability of the elderly in their family environment as long as possible, mutually benefiting the elderly and their families.
Older people looking for a day care home
Keywords: Idoso; Suporte social; Assistência diurna; Centro dia; Gerontologia; Elderly; Social support; Day care; Gerontology; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE SETORES ESPECIFICOS; CIENCIAS DA SAUDE; CIENCIAS HUMANAS; CIENCIAS SOCIAIS APLICADAS; OUTROS::CIENCIAS; CIENCIAS SOCIAIS APLICADAS::SERVICO SOCIAL::SERVICO SOCIAL APLICADO::SERVICO SOCIAL DA HABITACAO